QUANTITATIVE EVALUATION OF ROCK MASS BASED ON RMR, GSI AND SMR CLASSIFICATION IN DIORITE MINING AT THE SEKONGKANG REGION, WEST SUMBAWA DISTRICKT WEST NUSA TENGGARA PROVINCE - Arif Suryanegara, R.
The potential for minerals, especially minerals of classes A, B, and C, is found in West Sumbawa Regency, West Nusa Tenggara Province. These minerals include stone, sand/gravel, limestone, nickel, gold and copper which can be found around the research location. Mining practices, especially for class C minerals, are carried out traditionally using small-scale heavy equipment. The purpose of this research is to provide recommendations for good and safe mining based on the classification above. The aim of this research is to carry out rock mass classification analysis using the Rock Mass Rating(RMR) and Geological Strength Indeks(GSI) methods, to help determine slope classification using the Slope Mass Rating(SMR) method, and to determine the relationship between these values. The results of the weighting analysis with the RMR weight classification range from 65.33 to 80.18. In general, the rock mass is included in class I/very good, or the rock mass is in very good condition. From the results of the collapse probability analysis used, it is known that based on kinematic analysis with software that slopes T001, T003, T004, T005, T006 and T007, the probability of collapse that occurs is a rolling collapse and at the observation point, slope T002 is a plane collapse. From the results of the SMR weighting analysis, the classification of slopes T001, T002, T003, T004, T005, T006, and T008 is included in the very good slope classification, has a stable level of slope stability, the possibility of failure in the rock mass in some parts of the rock block, strengthening can be carried out accordingly. with the needs that occur at the research location. Meanwhile, slope T007 is classified as a good slope, a very stable slope category, there is no possibility of slope failure. Analysis of safety factors (FK) using rock mass using the RMR and GSI methods shows unstable slope conditions on slopes T001 and T008, respectively with safety factor values of 0.877 and 0.905, while on slopes T002 and T007 with FK values respectively 1.064 and 1.162 and on slopes T003, T004 and T005 have stable safety factor values for the two RMR and GSI methods, namely the FK values are 1.305, 5.772 and 1.428 respectively.